2018
DOI: 10.1016/j.jchf.2017.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Relative Impairments in Hemodynamic Exercise Reserve Parameters in Heart Failure With Preserved Ejection Fraction

Abstract: The most consistent and severe hemodynamic reserve abnormalities observed in patients with HFpEF were impairment in chronotropic reserve and exaggerated increase in pulmonary capillary wedge pressure with exercise. These may be important targets for therapeutic strategies to improve exercise tolerance in patients with HFpEF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 47 publications
2
61
0
2
Order By: Relevance
“…A high resting mPCWP and a pathological increase in mPCWP during exercise predict poor outcomes from HFpEF 168 , 249 , 263 . Patients with a normal mPCWP at rest (<12 mmHg) but a steep increase during exercise (to ≥25 mmHg) have a two‐fold increase in mortality 263 .…”
Section: Calculating and Interpreting The Hfa–peff Scorementioning
confidence: 99%
See 2 more Smart Citations
“…A high resting mPCWP and a pathological increase in mPCWP during exercise predict poor outcomes from HFpEF 168 , 249 , 263 . Patients with a normal mPCWP at rest (<12 mmHg) but a steep increase during exercise (to ≥25 mmHg) have a two‐fold increase in mortality 263 .…”
Section: Calculating and Interpreting The Hfa–peff Scorementioning
confidence: 99%
“…In a meta-analysis, exercise capacity in HFpEF was related to chronotropic incompetence, high mPCWP, blunted augmentation of arteriovenous oxygen-content difference (implying inadequate perfusion of exercising skeletal muscles), reduced stroke volume reserve, and pulmonary hypertension. 168 Changes in pulmonary artery pressure (PAP) on exercise are determined by the interplay between CO, pulmonary artery compliance, pulmonary vascular resistance, and mPCWP. The increase in PAP is flow-dependent so it is best reported in relation to the increase in CO; the upper limit of normal is +3 mmHg/L/min.…”
Section: Defining Aetiology and Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation
“…11 Similar to HFrEF, peak Q̇c and impaired peripheral oxidative capacity limit peak exercise performance in HFpEF patients. 7 9-17 While peak Q̇c is blunted due to chronotropic incompetence and impaired stroke volume reserve during maximal exercise, 12 it is unclear to what extent HFpEF patients experience impaired haemodynamic and metabolic function during submaximal exercise, similar to activities of daily living. In contrast to HFrEF, HFpEF patients consistently demonstrate normal augmentation of Q̇c during low-intensity submaximal exercise.…”
Section: Original Research Articlementioning
confidence: 99%
“…A recent meta-analysis indicates that HFpEF patients have normal or slightly smaller changes in a-vO 2 difference at peak exercise in the supine position, whereas during exercise in the upright posture (the position of most activities of daily living), a-vO 2 difference at peak exercise is consistently lower. 12 In regards to Q̇c, all studies to date have found that HFpEF patients display a preserved or exaggerated Q̇c response during submaximal exercise. 9 10 14 18 Specifically, the majority of these studies indicate that the rise in Q̇c in response to a change in VȮ 2 (Q̇c/VȮ 2 relationship) is preserved in HFpEF patients compared with healthy controls.…”
Section: Potential Mechanisms For Reduced Kinetics In Hfpefmentioning
confidence: 99%